Genomic Adaptation of Saccharomyces Species to Industrial Environments - Giannakou, Konstantina; Cotterrell, Mark; Delneri, Daniela (Frontiers in Genetics, 2020)
The budding yeast has been extensively studied for its physiological performance in fermentative environments and, due to its remarkable plasticity, is used in numerous industrial applications like in brewing, baking and wine fermentations. Furthermore, thanks to its small and relatively simple eukaryotic genome, the molecular mechanisms behind its evolution and domestication are more easily explored. Considerable work has been directed into examining the industrial adaptation processes that shaped the genotypes of species and hybrids belonging to the Saccharomyces group, specifically in relation to beverage fermentation performances. A variety of genetic mechanisms are responsible for the yeast response to stress conditions, such as genome duplication, chromosomal re-arrangements, hybridization and horizontal gene transfer, and these genetic alterations are also contributing to the diversity in the Saccharomyces industrial strains. Here, we review the recent genetic and evolutionary studies exploring domestication and biodiversity of yeast strains.